Assessment of biomethane potential of cotton stalk using response surface methodology - Yildirim, Oznur; Altinbas, Mahmut; Ozkaya, Bestami (INDERSCIENCE ENTERPRISES LTD, 2023)
Nowadays energy policies, providing sustainability criteria, encourage energy production from renewable resources. Cotton stalks are one of the most common agricultural wastes in Turkey and the world. Evaluating the potential of using cotton stalks in biomethane production is important in terms of both waste management and sustainable energy production. In this study, the optimum F/I and organic loading ratio were investigated for biomethane production from cotton stalk waste with response surface methodology (RSM). The R2 value, which shows the accuracy of the second-order polynomial equation obtained from the model, was found to be 0.9978 and 0.9876 for biomethane and VFA, respectively. As a result of thermal acid pre-treatment, the maximum biomethane potential (114.19 ml/g VS) was obtained from cotton stalk wastes under F/I 0.25 and OL 35 g VS/L conditions. In addition, changes in cotton stalk after pre-treatment were observed by FE-SEM and FTIR analysis. Biomethane production has been proven and modelled to be achievable using only the solid phase formed after pre-treatment.
Keywords: anaerobic digestion; biomethane; cotton stalk; response surface methodology; RSM; LIGNOCELLULOSIC BIOMASS; ANAEROBIC-DIGESTION; PRETREATMENT; DETOXIFICATION; CELLULOSE; RECOVERY; ETHANOL; Environmental Sciences & Ecology